Intranasal Inoculation of Cationic Crosslinked Carbon Dots‐Adjuvanted Respiratory Syncytial Virus F Subunit Vaccine Elicits Mucosal and Systemic Humoral and Cellular Immunity - Hong Lei; Aqu Alu; Jingyun Yang; Cai He; Jie Shi; Weiqi Hong; Dandan Peng; Yu Zhang; Jian Liu; Furong Qin; Xiya Huang; Chunjun Ye; et al. (MedComm)
ABSTRACT Respiratory syncytial virus (RSV) causes severe acute lower respiratory tract infections, especially in infants and the elderly. Developing an RSV vaccine that promotes a robust mucosal immune response is necessary to successfully prevent viral transmission and the development of severe disease. We previously reported that crosslinked carbon dots (CCD) may be an excellent adjuvant candidate for intranasal (IN) protein subunit vaccines. Considering the strong immunogenicity of RSV prefused F protein (preF), we prepared an IN RSV vaccine composed of the CCD adjuvant and the preF protein as antigen (CCD/preF) and evaluated the induced antigen‐specific humoral and cellular immunity. We found that IN immunization with the CCD/preF vaccine elicited strong serum IgG responses and mucosal immunity, including secreted IgA antibodies, tissue‐resident memory T (TRM) cells, and antigen‐specific B cells, which lasted for at least 1 year. In addition, a combination of intramuscular and IN immunization with CCD/preF vaccine induced stronger systemic and mucosal immunity. Together, this study proved the high immunogenicity of the CCD/preF vaccines and supported the university of the mucosal CCD adjuvant, supporting further development of the CCD/preF vaccine in larger animal models and clinical studies.